2014
DOI: 10.1002/jemt.22346
|View full text |Cite
|
Sign up to set email alerts
|

Super‐resolution imaging with stochastic single‐molecule localization: Concepts, technical developments, and biological applications

Abstract: Light microscopy has undergone a revolution with the advent of superresolution microscopy methods that can surpass the diffraction limit. These methods have generated much enthusiasm, in particular with regards to the new possibilities they offer for biological imaging. The recent years have seen a great advancement both in terms of new technological developments and exciting biological applications. Here, we review some of the important milestones in the field and highlight some recent biological applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…To determine the events that take place at the synapse leading to this decrease of surface NMDAR levels, we used single-molecule localization microscopy, in particular stochastic optical reconstruction microscopy (STORM) (Oddone et al, 2014; Rust et al, 2006). STORM revealed that under control conditions (neurons cultured in the presence of CSF without NMDAR antibodies), the NMDARs are organized in nanosized clusters along the dendrite (Figure 1A), which we refer to as nano-objects.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the events that take place at the synapse leading to this decrease of surface NMDAR levels, we used single-molecule localization microscopy, in particular stochastic optical reconstruction microscopy (STORM) (Oddone et al, 2014; Rust et al, 2006). STORM revealed that under control conditions (neurons cultured in the presence of CSF without NMDAR antibodies), the NMDARs are organized in nanosized clusters along the dendrite (Figure 1A), which we refer to as nano-objects.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison and advantages of different superresolution microscopy techniques are reviewed extensively elsewhere 16,18,19,23,35,36 . The main advantage of STORM on biological tissue is its unsurpassed single-molecule localization accuracy, and, consequently, the possibility of high-resolution analysis of molecular distribution.…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…SMLM is one of the main superresolution approaches, and it relies on determining the precise position of isolated images of single fluorophores 19 . One of its branches, STORM 3 , exploits the photoswitching behavior of certain organic dyes to achieve temporal separation of otherwise overlapping emitters.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve this, we must venture beyond the lateral resolution obtainable by conventional LM and confocal microscopy (about 250 nm). By using super-resolution microscopes, such as photoactivated localisation microscopy (PALM) and stochastic optical reconstruction microscopy (STORM), spatial resolution can be improved to 25-90 nm in order to obtain a more precise localisation of single molecules (Owen et al 2013;Klein et al 2014;Oddone et al 2014;Sibarita 2014). Resolution can be improved further, to 10 nm, by means of scanning electron microscopy (SEM) and to less than 1 nm by transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 98%